Succession planning: current practices, internal succession barriers and the relationship with intentions to leave within a public service in a developing country - Pita, Nomalinge Amelia (My University, 2015)
In today’s globally competitive and modern environments, organisational plans often fail due to the lack of succession planning. However, numerous organisations often fail to prepare for the inevitable departure of employees, especially in strategically high-level positions. Succession planning is a means of identifying critical management positions starting at lower level management and extending up to the highest position in an organisation. Unlike workforce planning, succession planning focuses more on advancing the employees’ skills in order to achieve the organisational objectives. There is no organisation that can exist forever in its present composition as there must be some form of succession or else the organisation will become obsolete. Succession planning plays an imperative role in today‘s competitive world. There are many factors that influence the stability of an organisational workforce, among which are illness and attrition. Another essential factor, which has taken the world by storm, is the retirement of the baby boomer generation in both in the private and the public sector. This is presenting a challenge within organisations, as they are going to lose talented and experienced employees and makes succession planning more needed more than ever before. Succession planning is an ongoing process that assists the organisation to align its goals with its workforce, as well as preserving the best talent for the future. It makes the organisation ready to face the challenges presented by the vacant key and critical positions. Succession planning is one of those human resource planning strategies utilised to forecast the talent demand that the organisation will require for achieving its future goals. The main purpose of this study was to examine the succession planning current practices and internal succession barriers, and determine their relationship with intentions to leave within the public service of a developing country. The research methodology used to conduct the study is a combination of a literature review and an empirical study. The probability sampling technique, which involves using simple random sampling, was utilised to select the sample for the study. The primary data were collected using a structured questionnaire. The measuringinstrument contained 25 items. The instrument was pilot-tested with 87 respondents one month prior to the main survey. The questionnaire was hand delivered to all the participants. For the main survey, data from 250 respondents were collected and analysed. Participants in the study involve officers, managers and directors in the public service of a developing country. Data were analysed with the Statistical Package for Social Sciences (SPSS) version 20.0. The Cronbach’s alpha coefficients of the various sections of the measuring instrument were computed to establish construct validity. Content validity of the scale was ascertained by pre-testing the questionnaire with employees in the public service. Exploratory factor analysis was conducted for variables in Section B of the research instrument. Convergent validity was assessed through correlation analysis using Pearson’s correlation coefficient in order to establish relationships between succession planning current practices and intentions to leave, as well as between internal succession barriers and intentions to leave the public service. Analysis was done using descriptive statistics on the demographics information of respondents. The results were also interpreted through the exploratory factor analysis, correlation and regression analysis. The results showed that two major factors of succession planning, namely replacement planning and grooming, correlate negatively with intentions to leave. The internal succession barriers also have a negative correlation with intentions to leave. Subsequent to these findings, it is recommended that the public service implement succession planning appropriately and eliminate the barriers thereof in order to retain its workforce. Based on the findings emanating from the empirical survey it was revealed that if succession planning is implemented appropriately and factors such as replacement planning and grooming are taken into consideration, employees holding key positions may be likely to be retained. Therefore, it was recommended that prior to undertaking succession planning a mission, vision and values that accommodate the contributions of employees should be developed. It was recommended also that when implementing succession planning, clear, transparent and objective criteria should be followed to achieve the optimal results. It is further recommended that the following succession planning best practices should be adopted by the public service to ensure that succession planning is implemented and practised successfully: Facilitation of an outside private consultant − for succession planning to be effective and rewarding in the public service it should be facilitated by an outside private consultant. Understanding of factors that influence succession planning − the public service should understand the necessity to know and address factors that influence willingness to share knowledge by employees. The study concludes by recommending that barriers that hinder succession planning should be avoided by adhering to the following suggestions: Longer terms of appointment should be provided for top public service employees Succession planning should be listed as one of the priorities in the public service strategic plan in order to be included in the budget Young vibrant and competent employees be motivated, groomed and prepared to apply for leadership or key positions in the public sector
M.. Tech. (Human Resource Management, Faculty of Management Sciences), Vaal University of Technology
Keywords: Succession planning; Critical management positions; 352.6; Civil service -- Personnel management -- South Africa; Public administration -- Management; Career development